Human activities as a driver of spatial variation in the trophic structure of fish communities on Pacific coral reefs. (25th September 2017) - Ruppert, Jonathan L. W.; Vigliola, Laurent; Kulbicki, Michel; Labrosse, Pierre; Fortin, Marie‐Josée; Meekan, Mark G.
Abstract: Anthropogenic activities such as land‐use change, pollution and fishing impact the trophic structure of coral reef fishes, which can influence ecosystem health and function. Although these impacts may be ubiquitous, they are not consistent across the tropical Pacific Ocean. Using an extensive database of fish biomass sampled using underwater visual transects on coral reefs, we modelled the impact of human activities on food webs at Pacific‐wide and regional (1, 000s–10, 000s km) scales. We found significantly lower biomass of sharks and carnivores, where there were higher densities of human populations (hereafter referred to as human activity); however, these patterns were not spatially consistent as there were significant differences in the trophic structures of fishes among biogeographic regions. Additionally, we found significant changes in the benthic structure of reef environments, notably a decline in coral cover where there was more human activity. Direct human impacts were the strongest in the upper part of the food web, where we found that in a majority of the Pacific, the biomass of reef sharks and carnivores were significantly and negatively associated with human activity. Finally, although human‐induced stressors varied in strength and significance throughout the coral reef food web across the Pacific, socioeconomic variables explained more variation in reef fish trophic structure than habitat variables in a majority of the biogeographic regions. Notably, economic development (measured as GDP per capita) did not guarantee healthy reef ecosystems (high coral cover and greater fish biomass). Our results indicate that human activities are significantly shaping patterns of trophic structure of reef fishes in a spatially nonuniform manner across the Pacific Ocean, by altering processes that organize communities in both "top‐down" (fishing of predators) and "bottom‐up" (degradation of benthic communities) contexts. Abstract : There are now very few (if any) places where human activities do not have an impact on coral reef ecosystems. Direct human impacts are the strongest in the upper part of the food web. Moreover, the importance of human populations as structuring forces within reef ecosystems is demonstrated by socioeconomic variables of human populations explaining as much or more variation in the trophic structure of reef fishes than habitat in a majority of the biogeographic regions. Our study highlights the need to tune management approaches regionally to not only account for account for differences in habitat and biogeography, but also for the socioeconomic factors of resident human populations.